Stomatal characterization, chlorophyll concentration and their relation with biomass production of Bouteloua curtipendula - Álvarez-Holguín, Alan; Morales-Nieto, Carlos Raúl; Corrales-Lerma, Raúl; Avendaño-Arrazate, Carlos Hugo; Rubio-Arias, Héctor Oswaldo; Villarreal-Guerrero, Federico (Agronomía Mesoamericana, 2018)
The stomatal characteristics and chlorophyll concentration are some of the main parameters, to determine plant productivity. The objective of the present study was to characterize the stomatal density and distribution to estimate the chlorophyll concentration and evaluate their effect on the biomass production of sideoatsgrama[Bouteloua curtipendula (Michx.) Torr.] genotypes. The experiment was performed from May to July 2015 under greenhouse conditions, at- the School of Animal Sciences and Ecology of the Autonomous University of Chihuahua, Mexico. Three commercial varieties were studied: El Reno, Niner, Vaughn and two native genotypes: E-689 and E-592 of side-oats grama. The variables evaluated were chlorophyll concentration index (CCI), stomatal density (SD), trichome density (TD), stomatal index (SI), and stomatal area (SA). These variables were related to biomass production (BP) applying regression analysis. SD and SI showed a negative effect on BP, while SA and CCI showed a positive effect. The genotype E-689 showed the lowest (p<0.05) SD and SI, with values from 152.7 to 275 stomatal/μm2 and from 13.41 to 16.03%, respectively. In addition, it also presented the highest (p<0.05) SA and BP, with values from 186.7 to 361.7 μm2 and 13.5 to 30.3 g, respectively. In conclusion, genotypes of side-oats grama with lower stomatal density and stomatal index and higher stomatal area and chlorophyll concentration index could produce higher amounts of biomass.